Women, fire, and dangerous things : what categories reveal about the mind - Lakoff, George (Chicago : University of Chicago Press, 1987)
Annotation pending.
Includes indexes.
Bibliography: p. 589-600.
Keywords: Psycholinguistics; Categorization (Psychology); Cognition; Thought and thinking; Reason; Psychology - Cognition; Language; Dyirbal / Djirbal / Jirrabul language (Y123) (Qld SE55-05); Language - Semantics